Hubungan Adanya Promosi Kesehatan Dan Riwayat Hipertensi Dengan Kejadian Pre Eklamsia Pada Ibu Inpartu Dalam Persalinan - Dewi Sartika Silaban, Anjelina Puspita Sari, Romlah, Titin (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
Preeclampsia is one of the complications of pregnancy that contributes significantly to maternal and infant morbidity and mortality. There are many factors that cause delivery by C-section, one of the indications for C-section is severe preeclampsia. One of the risk factors for PEB is a history of hypertension before or during pregnancy. The World Health Organization (WHO) reports that in 2023, the maternal mortality rate (MMR) worldwide reached 287,000 deaths due to complications during pregnancy and childbirth. This study aims to determine the relationship between health promotion and a history of hypertension with the incidence of PEB in pregnant women. This study uses an observational analytical design with a cross-sectional approach. The population in this study consisted of pregnant women and women in labor at specific health facilities during a specified period. The sample was taken using accidental sampling, resulting in a sample size of 50 respondents. Data were collected through structured interviews, questionnaires, and medical record reviews. The independent variables were health promotion and history of hypertension, while the dependent variable was the incidence of preeclampsia. Data analysis used the chi-square test at a significance level of p<0.05. The results of the study obtained a p-value of 0.004 for health promotion and a p-value of 0.026 for a history of hypertension in relation to the incidence of preeclampsia in mothers. It is hoped that this study will become a source of knowledge in providing education to mothers during pregnancy